L’expérience des francophones dans l’Est ontarien : importance des personnes pivots (usagers et intervenants) et influence des structures encadrant le système de santé et des services sociaux - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Le présent chapitre décrit l’expérience d’accès à des services sociaux et de santé en français de francophones de l’Est ontarien. Les expériences et les perspectives de 40 parents, aînés et proches aidants ont été recueillies à l’aide d’entrevues semi-structurées. Une analyse qualitative des verbatim ainsi qu’une analyse visuelle des trajectoires d’un sous-groupe de neuf participants ont permis de faire ressortir les facilitateurs et les défis d’accès aux services en français rencontrés par ces usagers, à partir de leur perspective ou de celle de leur proche aidant. Plus spécifiquement, ce chapitre met l’accent sur les éléments facilitateurs dans le but d’en tirer des leçons pour améliorer les services sociaux et de santé en langue officielle en situation minoritaire. Mots-clés : accès aux services en français, francophones Ontario, recherche qualitative.

The experience of Francophones in Eastern Ontario: The importance of key facilitators (service users and providers) and the influence of structures supporting the health and social services system - Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Lagacé, Josée; Arcand, Isabelle; Kubina, Lucy-Ann; Benoît, Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)

Enabling the participation of marginalized populations: Case studies from a health service organization in Ontario, Canada - Montesanti, Stephanie. R.; Abelson, Julia; Lavis, John. N.; Dunn, James. R. (Health Promotion International, 2017)
We examined efforts to engage marginalized populations in Ontario Community Health Centers (CHCs), which are primary health care organizations serving 74 high-risk communities. Qualitative case studies of community participation in four Ontario CHCs were carried out through key informant interviews with CHC staff to identify: (i) the approaches, strategies and methods used in participation initiatives aimed specifically at engaging marginalized populations in the planning of and decision making for health services; and (ii) the challenges and enablers for engaging these populations. The marginalized populations involved in the community participation initiatives studied included Low-German Speaking Mennonites in a rural town, newcomer immigrants and refugees in an urban downtown city, immigrant and francophone seniors in an inner city and refugee women in an inner city. Our analysis revealed that enabling the participation of marginalized populations requires CHCs to attend to the barriers experienced by marginalized populations that constrain their participation. Key informants outlined the features of a ‘community development approach’ that they rely on to address the barriers to marginalized peoples' involvement by strengthening their skills, abilities and leadership in capacity-building activities. The community development approach also shaped the participation methods that were used in the engagement process of CHCs. However, key informants also described the challenges of applying this approach, influenced by the cultural values of some groups, which shaped their willingness and motivation to participate. This study provides further insight into the approach, strategies and methods used in the engagement process to enable the participation of marginalized populations, which may be transferable to other health services settings.

Cognitive health initiative for Francophone seniors in the GTA - Reflet Salvéo; Entité 4 (Options fo Service Models, 2017)

Guide de planification et de prestation des soins de longue durée en français. Leçons tirées du pavillon Omer Deslauriers de Bendale Acres et d'autres services de santé en français pour aînés au Canada - Réseau franco-santé du Sud de l’Ontario (2017)

Maintien à domicile : capacité d’offre de services communautaires actuels et futurs au Nouveau-Brunswick - Thériault, Danielle; Dupuis-Blanchard, Suzanne (Service Social, 2017)
La présente étude comporte trois objectifs : 1) déterminer l’état actuel des services offerts pour le maintien à domicile; 2) explorer la nature de la planification des services futurs pour le maintien à domicile; et 3) exposer les défis reliés aux services et les moyens qui s’offrent aux organismes pour que les services répondent le plus efficacement possible aux besoins des personnes âgées francophones. De type séquentiel exploratoire mixte, cette étude a permis de recueillir des données qualitatives pour bonifier des résultats quantitatifs. Quarante-neuf gestionnaires ont répondu au questionnaire en ligne et 11 entrevues ont été réalisées. Huit thèmes communs ont été dégagés en lien avec les objectifs, thèmes qui montrent une préoccupation pour la viabilité des services communautaires en maintien à domicile. Mots-clés : personnes âgées, maintien à domicile, planification, gestion, organismes communautaires, francophones